2018
DOI: 10.33369/joall.v3i2.6846
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teachers’ Direct and Indirect Feedback on Student’ S Writing Ability

Abstract: This study is intended to find out any difference in effectiveness between direct and indirect feedback on students’ writing ability. The design was Quasi-Experiment. The population consisted of the students of the X class of SeniorHigh School 4, Rejang Lebong, Curup, Indonesia. The samples comprised 32 students in group 1 and 32 Students in group 2. The instrument was a writing test. In the data analysis, the researcher used the normality, homogeneity,and t-test.These were calculated and analyzed by using SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For this feedback to be effective, it must be lucid and precise, ensuring students comprehend the language and symbols employed by the teacher. As elucidated by Latifah et al (2018), teachers' belief in offering feedback fosters mindfulness and self-learning, enabling students to discern the imperfections within their work. This represents one of the means through which teachers can aid students in identifying the shortcomings in their own creations.…”
Section: Teachers' Belief and Practices Of Written Corrective Feedbac...mentioning
confidence: 99%
“…For this feedback to be effective, it must be lucid and precise, ensuring students comprehend the language and symbols employed by the teacher. As elucidated by Latifah et al (2018), teachers' belief in offering feedback fosters mindfulness and self-learning, enabling students to discern the imperfections within their work. This represents one of the means through which teachers can aid students in identifying the shortcomings in their own creations.…”
Section: Teachers' Belief and Practices Of Written Corrective Feedbac...mentioning
confidence: 99%
“…As technology grow and evolve, the use of technological tools to support statistical investigations is a part of researchers' way to present convincing reports and tasks (Makar, 2018). The use of Statistical Package for Social Science (SPSS) version 26 was used as the technology that could advise the researchers to minimize statistical calculation mistakes in handling large data sets and this software is employed by many researchers in the same field as the statistical calculation application and data presentation (Latifah et al, 2018;Mahande et al, 2019;Qutob & Madini, 2020). The SPSS version 26 was implemented since this is the latest version of SPSS when this research was conducted.…”
Section: Figure 1 a Framework Of Statistical Investigation (J M Watso...mentioning
confidence: 99%
“…The mark appears to be their main concern (Dlaska, & Krekeler, 2017). However, it is important to note that this lack of interest could be ascribed to a lack of training or support in how to use feedback (Latifah, Suwarno & Diani, 2019;Mahsood, Jamil, Mehboob, Kibria, & Rehman Khalil, 2018).…”
Section: Information On the Processmentioning
confidence: 99%
“…Although it is often argued that students' self-assessment skills should be much more actively strengthened by their teachers (Bourke, 2018), this is still far from reality in many educational Indirect Feedback: A Dialoguing Approach … 5 settings. IF can help to overcome this deficit by training students in appropriate techniques that, as Latifah et al (2019) have demonstrated, can improve performance in final examinations.…”
Section: The Development Of Self-assessment (Reflection) In Learningmentioning
confidence: 99%